2000
DOI: 10.1111/j.1749-6632.2000.tb06833.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanisms of Gas Hydrate Formation and Dissociation with Inhibitors

Abstract: A common chemical used in petroleum industry for preventing hydrates is methanol. Other alcohols and glycols (thermodynamic inhibitors) can also be used to shift hydrate formation to lower temperatures and higher pressures. A new family of chemicals called kinetic inhibitors delays the formation of hydrates, but does not change the equilibrium formation conditions. We have constructed several new types of apparatus and present results on the kinetics of hydrate formation and dissociation in static and dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 3 publications
3
39
0
Order By: Relevance
“…For oil field operators, the existence of multiple melting peaks means the elevated stability with chemical inhibitors which renders their use more challenging. Observations in experiments in stirred vessels were consistent with the calorimetric observations showing a two-stage decomposition for hydrate prepared in the presence of chemical inhibitors (Daraboina et al, 2011b;Ohno et al, 2010) and 5 C higher melting temperature compared to hydrate prepared in pure water (Makogon et al, 2000). It should be noted that the experiments reported in (Daraboina et al, 2011b) and (Daraboina et al, 2011a) were done with a methane/ethane/propane mixture and those in (Makogon et al, 2000) with a natural gas mixture.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…For oil field operators, the existence of multiple melting peaks means the elevated stability with chemical inhibitors which renders their use more challenging. Observations in experiments in stirred vessels were consistent with the calorimetric observations showing a two-stage decomposition for hydrate prepared in the presence of chemical inhibitors (Daraboina et al, 2011b;Ohno et al, 2010) and 5 C higher melting temperature compared to hydrate prepared in pure water (Makogon et al, 2000). It should be noted that the experiments reported in (Daraboina et al, 2011b) and (Daraboina et al, 2011a) were done with a methane/ethane/propane mixture and those in (Makogon et al, 2000) with a natural gas mixture.…”
Section: Introductionsupporting
confidence: 79%
“…Observations in experiments in stirred vessels were consistent with the calorimetric observations showing a two-stage decomposition for hydrate prepared in the presence of chemical inhibitors (Daraboina et al, 2011b;Ohno et al, 2010) and 5 C higher melting temperature compared to hydrate prepared in pure water (Makogon et al, 2000). It should be noted that the experiments reported in (Daraboina et al, 2011b) and (Daraboina et al, 2011a) were done with a methane/ethane/propane mixture and those in (Makogon et al, 2000) with a natural gas mixture. There was no explanation about the higher melting temperature in (Daraboina et al, 2011a) whereas the results reported in (Daraboina et al, 2011b;Makogon et al, 2000) were interpreted in terms of compositional and structural changes (Daraboina et al, 2011c;Ohno et al, 2012).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…At high pressures and low temperatures, as is the case with oil production and deep-sea transportation, hydrates constantly occur when water hydrogen bonds with the hydrocarbons in gas and oil products. In sufficient quantities these hydrates can completely block pipelines by agglomerating to create very stable, ice-like plugs, leading to disruptive and costly production stoppages [14]. Dendritic polymers can act as antiagglomerants or "surfactants" by preventing large hydrates from forming and keeping small crystals suspended in the production flow [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the time required for hydrate formation initiation (induction time) and the rate of growth of hydrate crystals are two time dependent fundamental factors which should be considered in hydrate kinetic studies (Englezos, 1993). Nucleation and growth may be affected by many factors, such as subcooling, pressure, temperature, previous history of water, composition, and state of the gas hydrate forming system (Makogon et al, 2000). All these factors limit the experimental research activities of hydrate formation kinetics.…”
Section: Hydrate Formation Kineticsmentioning
confidence: 99%